O “giro retórico” de Nietzsche - Casares, Manuel Barrios (2019)
Through the influence of the early German Romanticism and the position of Nietzsche’s thought within the history of metaphysics, the author aims at showing the fundamental role of rhetoric in the philosopher’s investigation on language, science and truth. Far from being just a propensity of his early studies, Nietzsche’s rhetorical perspective exerts, in the author’s view, a great influence on his whole work as a support in the battle against metaphysics.